APPLICATION OF MACROMEDIA FLASH LEARNING MEDIA IN INCREASING STUDENTS' INTEREST IN ICT SUBJECTS AT SMK NEGERI 6 SERANG IN ACADEMIC YEAR 2022/2023 - Tuniah; Desty Endrawati Subroto; Mohamad Bayi Tabrani (Cakrawala Pedagogik, 2023)
This study aims to obtain information on increasing student interest in Information and Communication Technology subjects at SMK Negeri 6 Serang City by using macromedia flash learning media. The method used in this study is a qualitative descriptive method, namely a research method that seeks to collect data from the phenomenon being investigated. This research was conducted at SMK Negeri 6 Kota Serang and the objects studied were limited to students of class X TKJ 1 and X TKJ 2 with a total of 36 students per class. Collecting data using the method of observation, interviews, questionnaires and documentation. Based on the research results, it is known that most of the students (83.3%) are very interested in learning to use learning media, especially macromedia flash. Macromedia flash is a media presentation that combines audio-visual technology such as sound, animation and text that can be used in the teaching and learning process. With Macromedia Flash it is easier for students to understand and accept the material taught by the teacher. This can be seen from the results of observations of the learning process which shows that students are more enthusiastic and enthusiastic, as well as active and creative in learning. This is supported by the results of interviews and questionnaires with students who explained that students really enjoyed learning to use Macromedia Flash because it looks attractive and easy to understand.